2011
DOI: 10.1073/pnas.1107748108
|View full text |Cite
|
Sign up to set email alerts
|

Striatal origin of the pathologic beta oscillations in Parkinson's disease

Abstract: Enhanced oscillations at beta frequencies (8-30 Hz) are a signature neural dynamic pathology in the basal ganglia and cortex of Parkinson's disease patients. The mechanisms underlying these pathological beta oscillations remain elusive. Here, using mathematical models, we find that robust beta oscillations can emerge from inhibitory interactions between striatal medium spiny neurons. The interaction of the synaptic GABAa currents and the intrinsic membrane M-current promotes population oscillations in the beta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

25
303
0
3

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 292 publications
(331 citation statements)
references
References 44 publications
25
303
0
3
Order By: Relevance
“…An intermediate view, supported by the model presented here, is that beta emerges in the neocortex but is dependent on extrinsic synaptic drive that could originate from basal ganglia/ thalamus. Consistent with the first view, beta has been robustly observed in LFP signals from basal ganglia nuclei including the subthalamic nucleus, striatum, and globus pallidus (18,19), and computational models have proposed mechanisms by which beta rhythms can emerge via interactions within and between these circuits (20,21). Other studies have suggested that the neocortex itself has unique properties that generate beta rhythms through spike-mediated synaptic and electrical interactions within local circuits (22)(23)(24)(25) or that beta in early-sensory neocortical areas could be driven in a top-down manner from frontal cortex during attentive states (26).…”
mentioning
confidence: 54%
See 3 more Smart Citations
“…An intermediate view, supported by the model presented here, is that beta emerges in the neocortex but is dependent on extrinsic synaptic drive that could originate from basal ganglia/ thalamus. Consistent with the first view, beta has been robustly observed in LFP signals from basal ganglia nuclei including the subthalamic nucleus, striatum, and globus pallidus (18,19), and computational models have proposed mechanisms by which beta rhythms can emerge via interactions within and between these circuits (20,21). Other studies have suggested that the neocortex itself has unique properties that generate beta rhythms through spike-mediated synaptic and electrical interactions within local circuits (22)(23)(24)(25) or that beta in early-sensory neocortical areas could be driven in a top-down manner from frontal cortex during attentive states (26).…”
mentioning
confidence: 54%
“…This mechanism may not account for beta at different recording scales or behavioral states [e.g., motor hold conditions (27,28) or up-states (47)] or in other brain networks, particularly those without spatially aligned PNs such as inhibitory networks in the striatum, where other mechanisms have been proposed (21). Prior modeling and experiments, primarily from slice recordings, have established that neocortical beta rhythms can emerge from the spiking interactions of local excitatory and inhibitory populations (22)(23)(24)(25)(26).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…25,[40][41][42][43][44] Transitions between dynamic regimes have been observed during sleep, and abnormal transitions have been associated with sleep disorders. 26,[45][46][47][48][49][50][51] Finally, the slow waves of cortical spreading depression 52 underlie the reduction of excitability in neuronal tissue associated with migraine, 53,54 in particular, migraine with aura. 52 On the three fronts of modeling, computation, and experiment, there have been a series of important recent advances, and many new avenues of research have emerged.…”
Section: Introductionmentioning
confidence: 99%